Crystallization kinetics and nanomechanical behavior of biobased poly(ethylene 2, 5‐furandicarboxylate) reinforced with carbon nanotubes. Issue 1 (26th October 2022) - Kourtidou, Dimitra; Grigora, Maria‐Eirini; Papadopoulos, Lazaros; Tzetzis, Dimitrios; Bikiaris, Dimitrios N.; Chrissafis, Konstantinos
Abstract: Poly(ethylene 2, 5‐furandicarboxylate) (PEF) is one of the most widely known biobased polyesters due to its outstanding gas barrier and mechanical properties, making it the number one candidate to substitute poly(ethylene terephthalate) (PET). However, its crystallization from the melt is much slower compared to PET, affecting the overall processing of the material. For this reason, PEF nanocomposites containing various carbon nanotubes (CNTs) loadings (0–2.5 wt%) have been in situ synthesized in this work. Differential scanning calorimetry (DSC) measurements were conducted to evaluate all the prepared materials' isothermal and nonisothermal crystallization kinetics. Isothermal kinetics using the Avrami and Hoffman–Lauritzen (H–L) theories suggested that the nucleating effect of the CNTs is more profound during the crystallization from the melt, where the higher crystallization rate is observed in the case of PEF/2.5 CNTs nanocomposite. This is also confirmed by the nonisothermal crystallization analysis. The nucleation activity of the filler was estimated by Dobreva's method, which revealed that higher CNTs (1 and 2.5 wt%) content presents increased nucleation efficiency during the process. The nanoindentation results showed that the addition of CNTs in the PEF matrix enhanced the nanomechanical properties of PEF. Semicrystalline samples presented significantly higher hardness ( H ) and elastic modulus ( E ) values compared to their amorphous counterparts, where semicrystalline PEF/2.5 CNTs nanocomposite presented 135% increase of E compared to the amorphous neat PEF. Abstract : Incorporating carbon nanotubes as a filler in biobased poly(ethylene 2, 5‐furandicarboxylate) accelerated the crystallization from the melt and glass and reinforced its nanomechanical properties.